Nutritional Health Perspective of Natto: A Critical Review - Muhammad Afzaal; Farhan Saeed; Fakhar Islam; Huda Ateeq; Aasma Asghar; Yasir Abbas Shah; Chigozie E. Ofoedu; James S. Chacha (Biochemistry Research International)
Natto, a traditional soy food fermented by Bacillus subtilis, is made by steaming or cooking soaked soybean seeds, inoculating them with the bacteria, and then letting them sit for an incubation period. Natto soya has grown popular because of its nutritional importance and health advantages. As a result, farmers have more opportunities, thanks to the natto soybean market. For the natto soybean market to remain stable and grow, improved soybean cultivars with enhanced natto quality traits are essential. Natto’s high-quality attributes are influenced by the bacteria strain, processing parameters, and soybean variety. Natto has a specific flavor and aroma with a slimy, sticky consistency. Natto possesses various therapeutic potentials and contains a range of essential nutrients and bioactive compounds, i.e., nattokinase, soybean isoflavone, γ-polyglutamic acid, vitamin K2, and biogenic amines. Bacterial species, processing conditions, and cultivars of soybean determine the quality characteristics of natto. Natto food is higher in menaquinone-7 and contains 100 times more menaquinone-7 than most cheeses. The present review highlights the production technology, microbiology, nutritional composition, and therapeutic potentials of natto.